2017
DOI: 10.1016/j.jcat.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the promoting effect of Mn on a Pt/C catalyst for the steam and aqueous phase reforming of glycerol

Abstract: The catalytic performances in steam reforming (SR) and aqueous phase reforming (APR) of glycerol of a bimetallic Pt-Mn catalyst supported on activated carbon are investigated and correlated with the surface properties of the catalyst. Under SR conditions, Mn showed a significant promoting effect over Pt/C, both in terms of hydrogen production rate and conversion, with a higher selectivity toward the glycerol dehydration products. Upon addition of Mn the amount of strong Lewis acid sites increased, promoting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…On the other hand, the use of Ce or Ce-Zr oxides provides good results, due to the good thermal and mechanical resistance and redox properties of Ce. Moreover, Mg and Mg-Al oxides are used to provide basic sites for the catalyst, improving H 2 formation and limiting hydrocarbon production and subsequent coke deposition on the catalyst surface, as many studies have pointed out [57,91,93]. On the contrary, the higher the acidity of the catalyst, the higher their affinity for coke deposition [20].…”
Section: Nice X Al Metal Oxidesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the use of Ce or Ce-Zr oxides provides good results, due to the good thermal and mechanical resistance and redox properties of Ce. Moreover, Mg and Mg-Al oxides are used to provide basic sites for the catalyst, improving H 2 formation and limiting hydrocarbon production and subsequent coke deposition on the catalyst surface, as many studies have pointed out [57,91,93]. On the contrary, the higher the acidity of the catalyst, the higher their affinity for coke deposition [20].…”
Section: Nice X Al Metal Oxidesmentioning
confidence: 99%
“…It usually contains VIII group metals, or they can be bimetallic catalysts. Moreover, the use of Ni-based catalysts and other X group metals is frequent due to their activity and selectivity[20,93];• It should have good support properties (dispersion of the active phase, co-catalytic sites, etc. ); •…”
mentioning
confidence: 99%
“…The generation of H 2 and CO 2 by ethanol APR is an ideal situation. Pt-based catalysts are a type of noble metal catalysts that can be used in ethanol reforming-based hydrogen preparation [29][30][31][32]. During the hydrogen generation via ethanol reforming on Pt-based catalysts, the O-H and C-H of ethanol needed similar energy, but Pt-C was more stable than Pt-O and more likely to be formed [33,34].…”
Section: Catalytic Activity Of Catalystsmentioning
confidence: 99%
“…Co 2 MnO 4 exhibited a desirable effect in ethanol steam reforming (ESR) and postponed catalyst deactivation 22. It was found that Mn in a Ce‐Mn composite as a catalyst in various reactions played an important role in water dissociation and easier CO oxidation 23–25. A highly favorable influence of Mn on CuZn at low temperature in ESR was also proved 26.…”
Section: Introductionmentioning
confidence: 98%